Lung cancers detected by screening with spiral computed tomography have a malignant phenotype when analyzed by cDNA microarray - Bianchi, F; Hu, J; Pelosi, G; Cirincione, R; Ferguson, M; Ratcliffe, C; Di Fiore, P; Gatter, K; Pezzella, F; Pastorino, U (2004)
Purpose: Spiral computed tomography (CT) can detect lung cancer at an early stage, but the malignant potential is unknown. The question is, as follows: do these small lesions have the same lethal potential as do symptomatic tumors? Experimental Design: We used a cDNA microarray platform and compared the gene expression profile of spiral CT-detected lung carcinomas with a matched case-control population of patients presenting with symptomatic lung cancer. Results: CT-detected and symptomatic tumors have shown a comparable gene expression profile. Correspondence analysis has demonstrated that nine genes were differentially expressed, although with a high variability across the samples that prevented distinguishing the two groups of tumors. Analysis of these nine genes has suggested that early-detected tumors have higher levels of retinoic acid production and higher expression levels of caveolin 2, matrix Gla, and cystatin A, which are already known to be lost during tumor progression. Conclusions: All of the tumors observed are histologically malignant according to the WHO Classification. Early lung cancers that are detected by screening have a gene expression pattern similar to, but not identical to, that of symptomatic lung carcinomas.